An international review of the frequency of single-bicycle crashes (SBCs) and their relation to bicycle modal share. (9th January 2014) - Schepers, Paul; Agerholm, Niels; Amoros, Emmanuelle; Benington, Rob; Bjørnskau, Torkel; Dhondt, Stijn; de Geus, Bas; Hagemeister, Carmen; Loo, Becky P Y; Niska, Anna
Abstract : Objectives: To study cyclists' share of transport modes (modal share) and single-bicycle crashes (SBCs) in different countries in order to investigate if the proportion of cyclist injuries resulting from SBCs is affected by variation in modal share. Methods: A literature search identified figures (largely from western countries) on SBC casualties who are fatally injured, hospitalised or treated at an emergency department. Correlation and regression analyses were used to investigate how bicycle modal share is related to SBCs. Results: On average, 17% of fatal injuries to cyclists are caused by SBCs. Different countries show a range of values between 5% and 30%. Between 60% and 95% of cyclists admitted to hospitals or treated at emergency departments are victims of SBCs. The proportion of all injured cyclists who are injured in SBCs is unrelated to the share of cycling in the modal split. The share of SBC casualties among the total number of road crash casualties increases proportionally less than the increase in bicycle modal share. Conclusions: While most fatal injuries among cyclists are due to motor vehicle–bicycle crashes, most hospital admissions and emergency department attendances result from SBCs. As found in previous studies of cyclists injured in collisions, this study found that the increase in the number of SBC casualties is proportionally less than the increase in bicycle modal share.